Updating the NCTUns-6.0 tool to simulate parallel optical burst switching of all-optical ultra-dense WDM systems - Ibrahem Salih, Adnan; Abdelouhahab, Abid; A. Mostafa, Salama; Zaiter, Mohammed Joudah (Springer Nature, 2015)
Optical burst switching (OBS) is proposed as suitable switching architectures for directly transporting traffic over a bufferless wavelength division multiplexing (WDM) networks. Parallel optical burst switching (POBS) is a variant of the OBS model that takes this concept further by transmitting data bursts wavelength and time dimensions. However, there is a lack of simulator that simulates POBS networks. This paper presents an update to the conventional OBS model in the NCTUns-6.0 simulator (NCTUns-POBS). The NCTUns-POBS tool is capable of simulating POBS networks for ultra-denseWDM. It analyzes the features of POBS networks, enables to adjust the parameters of POBS networks and enhances their switching technology. To test and validate the performance of the tool, the proposed random wavelength assignment technique (RWAT) is compared with the existing sequential wavelength assignment technique (SWAT) of the POBS model and the conventional OBS model. The results of the simulation show that, the NCTUns-POBS successfully simulates the POBS networks in which the proposed RWAT enables the POBS to yield higher throughput compared to the existing SWAT and the OBS conventional technique